Permodelan Sebaran BOD dan COD Sebagai Parameter Kualitas Air Baku Sungai Awang Kabupaten Barito Timur Provinsi Kalimantan Tengah - Vidya Restu Wijaya; Nomeritae; Raden Haryo Saputra (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research aimed to modeling chemical parameters in water, consist of BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) in Awang River, at Hayaping Village, Awang District, East Barito Regency, Central Kalimantan Province. Apart from obtaining BOD and COD values ​​from laboratory and modeling results, this research also aimed to determine manning values ​​and dispersion coefficient (D). The results of longitudinal and transverse measurements as well as the measured discharge were used as input for flow modeling using HEC-RAS 1 D. The discharge at the monitoring point from the modeling results was then compared with the discharge from the measurements, to determine the magnitude of the manning value. Next, water quality modeling was carried out to determine the dispersion coefficient value so that the distribution of BOD and COD parameters from the modeling results approached to laboratory results. From laboratory results, BOD values ​​were obtained ranging from 5.8-9.0 mg/L and COD values ​​of 4.58 mg/L, manning values ​​of 0.03 and Dispersion coefficient values ​​of D=0.277.